Преглед на модерните финансиски технологии и употребата на концептот на отворени иновации во финансиските услуги - Jovevski, Dimitar; Kamenjarska, T. (Економски факултет - Скопје, Универзитет „Св. Кирил и Методиј“ во Скопје, 2020)
Nowadays, the art of innovation and its expressiveness play an essential role in the process of gaining a competitive advantage and improving financial performance. This paper discusses the basic concepts, importance, and upswing of the open innovation model in the modern economy. Moreover, it tries to differentiate the concepts of open and closed innovation in organizations. Open Innovation in the banking sector is tightly linked with the concept of open banking, which allows third-party developers to design and implement innovative applications or services with the use of open application programming interfaces (APIs). For the banks to improve their market position and enhance the competitive edge, they are imposed to digitalize their business process by building a collaborative climate with the fintech companies and third-party organizations. This paper aims to explore diverse approaches of developing a tech-driven strategy that amalgamates information technologies within the business operations to successfully meet the business requirements and needs of the company. We further attempt to provide a concise explanation of the recent technology trends in the financial services in several countries including the SEE region. Considering the increased demand for the implementation of technological innovations in the financial sector, we stress the importance of forming collaborative relationships with external stakeholders and incorporating the outside intellectual capital within organizations’ boundaries. To deal with the ever-changing customer requirements, financial institutions should incorporate technology as part of their central business activities. This will result in increased productivity and efficiency, timely service delivery, enhanced customer retention, multi- channel distribution network, higher
Keywords: open innovation, FinTech, digital transformation, financial institutions